2005
DOI: 10.1063/1.2140087
|View full text |Cite
|
Sign up to set email alerts
|

Marine diatoms as optical chemical sensors

Abstract: Complex micro- and nanostructured materials for optical sensing purposes are designed and fabricated using top technologies. A completely different approach to engineering systems at the nanoscale consists in recognizing the nanostructures and morphologies that nature has optimized during life’s history on earth. We have found that the photoluminescence emission from silica skeleton of marine diatoms Thalassiosira rotula Meunier is strongly dependent on the surrounding environment. Both the optical intensity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 11 publications
2
76
0
Order By: Relevance
“…A weak but clearly detectable broad autofluorescence emission band with maximum at 470 nm in the case of C. granii (figure 4) was measured. Interestingly, visible fluorescence was reported for diatoms before, but in some cases with other spectral characteristics [19][20][21][22][23]. The origin of this fluorescence is not clear but can in principle either arise from the organic matrix that may contain heterocyclic moieties [3] or from surface states in mesoporous silica [24,25].…”
Section: Variation Of the Amino Function In Rhodamine Stainsmentioning
confidence: 97%
“…A weak but clearly detectable broad autofluorescence emission band with maximum at 470 nm in the case of C. granii (figure 4) was measured. Interestingly, visible fluorescence was reported for diatoms before, but in some cases with other spectral characteristics [19][20][21][22][23]. The origin of this fluorescence is not clear but can in principle either arise from the organic matrix that may contain heterocyclic moieties [3] or from surface states in mesoporous silica [24,25].…”
Section: Variation Of the Amino Function In Rhodamine Stainsmentioning
confidence: 97%
“…In 2005, De Stefano et al [14] found that diatom frustules emit 500 nm wavelength blue light after being illuminated with an UV light of 325 nm wavelength, this is known as the PL phenomenon. The peak of the PL spectrum varies when the frustules are surrounded by different gases or vapors (e.g.…”
Section: Potential Of Diatom Frustules In Device Applicationmentioning
confidence: 99%
“…The cell wall of a diatom known as the frustule, has a transparent structure composed of amorphous silica [6]. The frustule has good mechanical strength [7,8], a variety of three-dimensional (3D) shapes [9,10], multi-level nanopores and microstructures [11,12], large surface area and unique optical properties [13][14][15], making it a potential novel functional material for bio-manufacturing. Studies on theoretical understanding, manufacturing methods and functionalization of diatom frustules are ongoing.…”
mentioning
confidence: 99%
“…To date, the use of diatoms as key components in a variety of application areas has been reported. For example, in applications to sensing technology, diatoms have been employed as the sensing components in immunoassays and gas sensors [10][11][12][13][14] . Furthermore, in work by Lin et al 11 , diatom frustules have been employed in electrochemical impedance sensing and have been found to significantly improve performance, including sensitivity, response time, and dynamic range, compared with existing approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the ability to manipulate the frustules on a large scale, combined with simple arraying techniques 20 , may enable the development of practical, real-world applications using diatoms. However, despite the promise of the use of diatom frustules in a variety of areas, the unique properties of diatoms have typically only been studied on the scale of a single diatom frustule (requiring only individual diatom alignment) [6][7][8][10][11][12][13][14][15][16] or as bulk materials (requiring no significant alignment) 17 .…”
Section: Introductionmentioning
confidence: 99%